KOMPILASI HUKUM EKONOMI SYARI’AH (Analisa Terhadap Kekuatan Hukum dan Materinya) - Hasneni, Hasneni (Alhurriyah, 2016)
The economic development of Islam lately very rapidly, both in the academic level as well as a valid system at the global level. In Indonesia, the institutional practice of law mu'amalah. Muamalah started since the establishment of Bank Indonesia (BMI) in 1990. This was followed by a financial institution of Sharia (LKS) others. However, the fact it has urged the clergy and framers of law in Indonesia to make regulations relating to the settlement of the case in such issues, especially those related to economic practice. Thus came the fatwas of innovative products and designs multi revolutionarily of the contract. In the next phase in 2008 was born the rules issued by the Supreme Court, the Economic Law Compilation of Sharia (KHES). This paper wants to present about the fatwa forms and regulations that must have a theoretical basis of Shariah which has its own characteristics that distinguish it from other Islamic country mua'amalah rules ever